OLYMPIC EDUCATION IN RUSSIAN FEDERATION (Fiep Bulletin - online, 2014)
Nowadays the ideas of the Olympic Games traditions and their pedagogical values for children and youth are topical. International and National Olympic Committees must propagate the Olympism and Olympic education according to the Olympic Charter. Olympic education is determined as a system of Olympic movement knowledge diffusion. It is widely known all over the world that Olympic education is an important part of upbringing, as it helps to form harmonious developed personality and promotes the idea of a healthy lifestyle. Examples of Olympic winners and heroes influence children positively and effectively. Different national systems of education suggest keeping “Olympic days”, “Olympic lessons” and other extracurricular activities. How can we get school children to know about Olympism? At physical education! We have created a complete set of physical education study-books, which are recommended to 6-10-year-olds and their parents. The Olympic Games information is presented in three doses (chapters, items inside chapter and Olympic facts or pictures) and in three types of presentation (description, photos and Olympic examples). First-graders get to know about exciting moments of Olympic Games that arise children’s interest to sport and Olympism. The concept of Olympic Games, their ideas and their programme are introduced to second year schoolchildren. In third and fourth year schoolbooks we continue to describe Olympic  programmes and non-sporting part of the Olympic Games, their symbols and ceremonies. The connection between ancient and modern Olympic Games is shown. Special attention is paid to the Fair Play principles. The complete set of study-books was published in 2013. Russian children will start using them this year. We hope our system will bring positive results.
Keywords: Olympic Games; Olympic education; Primary school; Physical education.